Measuring and analyzing the effect of foreign debt on the gross domestic product in Morocco for the period 1990-2017 using the ARDL Test - Hamad, Mokheef Jasim; Mhmood, Muthanna Mayoof; Hassan, Fouad farhan (Journal of Economics and Administrative Sciences, 2021)
The research aims to identify the magnitude of the impact of external debt on the gross domestic product in Morocco, and the importance of research lies in the role that external debt plays in addressing structural imbalances, if it is best disposed of according to well-studied economic plans by specialists in this regard, especially if these debts are directed with Other resources, as it helps pay the costs of these debts (debt servicing) that the external debt also raises the level of gross domestic product, and the research starts from the hypothesis that: There is an effect of foreign debt on the GDP in Morocco, has contributed in one way or another to The exacerbation of the external debt, which affected the macro variables, of the Moroccan economy, and became unable to fulfill the debt maturities and its assets, and attempted to resort to rescheduling its debts according to unfair terms with the aim of reducing the severity of the debt, as statistical and standard tools were used, represented by testing the unit root to determine the dormancy of the time series and by accreditation On the methodology of (Dickie Fuller) expanded method, and to know the equilibrium relationship between the study variables, as the ARDL model was relied upon, the study found a relationship A long-term equilibrium (joint integration) between the study variables (independent and dependent), the statistical value of (F) reached (6.06), which is greater than the smallest value (3.29) and the maximum (4.37) at a significant level (1%). This indicates the existence of a long-term equilibrium relationship (a co-integration relationship) between the study variables in the long term. The time series of variables (Y, X1, X2, X3) is not stable at the level, while the time series of the independent variable (X4) is stable at the level. With a breaker and without a breaker and a time trend at a significant level (1%, 5%), and after taking the first difference of the variables (Y, X1, X2, X3), it stabilized at a significant level (1%, 5%, 10%) with the presence of a breaker and a breaker and a time trend Without a break and a time trend. It is evident from the two tests (CUSUM) and (CUSUM of Squares) that there are stability and consistency in the model for the short term and there is no stability in the long term. The most important recommendations are directing foreign debts to productive economic sectors, in a way that leads to creating added value and paying attention to foreign debts, directing them towards important priorities and maintaining the stability of macroeconomic variables, and moving away from debts with high conditionalities that restrict the country’s economy and falling into a debt trap